2021
DOI: 10.3389/fpsyt.2021.708426
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Impact of COVID-19 Racial and Ethnic Discrimination Against Asian American and Pacific Islanders

Abstract: Hate crimes against Asian American/Pacific Islanders (AAPIs) have surged in the United States during the COVID-19 pandemic to alarming new levels. We analyzed data from the Healthy Minds Study, and found that COVID-19 related racial/ethnic discrimination was associated with greater odds of having depression, anxiety, non-suicidal self-injury, binge drinking, and suicidal ideation among AAPI university students (N = 1,697). Findings suggest that the COVID-19 pandemic precipitated discrimination, which has been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 12 publications
5
28
0
Order By: Relevance
“…The indirect effects for anxiety and depression suggest that racial discrimination puts some KA at a higher risk for anxiety and depression, and higher levels of anxiety and depression are associated with poorer life satisfaction. Our findings are consistent with previous studies indicating that Asian Americans reported higher levels of depression (Litam & Oh, 2020;Nadimpalli et al, 2016;Zhou et al, 2021), higher levels of anxiety Nadimpalli et al, 2016;Zhou et al, 2021), and lower levels of life satisfaction (Tummala-Narra et al, 2018), following experiences of racial discrimination. Our results contribute to the existing literature and provide mental health professionals with critical insight into This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The indirect effects for anxiety and depression suggest that racial discrimination puts some KA at a higher risk for anxiety and depression, and higher levels of anxiety and depression are associated with poorer life satisfaction. Our findings are consistent with previous studies indicating that Asian Americans reported higher levels of depression (Litam & Oh, 2020;Nadimpalli et al, 2016;Zhou et al, 2021), higher levels of anxiety Nadimpalli et al, 2016;Zhou et al, 2021), and lower levels of life satisfaction (Tummala-Narra et al, 2018), following experiences of racial discrimination. Our results contribute to the existing literature and provide mental health professionals with critical insight into This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionsupporting
confidence: 93%
“…This study examined the relationship between COVID-19-related racial discrimination on anxiety, depression, and life satisfaction among KA and explored the buffering effect of ethnic identity and coping strategies. Similar to past studies (Hwang & Goto, 2008; Litam & Oh, 2021; Nadimpalli et al, 2016; Zhou et al, 2021), there was a positive and significant relationship between racial discrimination and anxiety and depression. COVID-19-related racial discrimination also had negative impacts on life satisfaction via increased levels of depression and anxiety.…”
Section: Discussionsupporting
confidence: 86%
“…Of particular note, the heightened anti-Asian racism throughout the COVID-19 pandemic has been associated with an increase in depression and anxiety in the Asian American community, further highlighting the need for physicians to screen effectively for mental health symptoms in this population. 20 …”
Section: Introductionmentioning
confidence: 99%
“…CHATogether ’s virtual space has also given AAPI youth the opportunity to cultivate their cultural pride and showcase their own projects with the CHATogether mentorship. As detailed in the Methods section, CHATogether has been uniquely built to handle complicated AAPI family conflicts, help bridge the acculturative gap between parents and children, and break down the stigma of difficult conversations surrounding topics such as racial bullying, suicide, and gender dysphoria [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%